Difference in the frequency of pouchitis between ulcerative colitis and familial adenomatous polyposis: is the explanation in peripouch fat?. (10th May 2019) - Gao, X. H.; Li, J. Q.; Khan, F.; Chouhan, H.; Yu, G. Y.; Remer, E.; Stocchi, L.; Hull, T. L.; Shen, B.
Abstract: Aim: Patients with ulcerative colitis (UC) have an unexplained higher incidence of pouchitis and a greater amount of peripouch fat compared with patients with familial adenomatous polyposis (FAP). The aims of this study were to compare the peripouch fat areas between patients with UC and patients with FAP, and to explore relationship between peripouch fat and pouchitis or chronic antibiotic‐refractory pouchitis (CARP). Method: Patients with an abdominal CT image from our prospectively maintained Pouch Database were included. Abdominal fat and peripouch fat were measured on CT images at different levels or planes. Comparisons of peripouch fat and CARP were performed before and after propensity score matching. Results: A total of 277 patients with UC and 40 patients with FAP were included. Compared with patients with FAP, patients with UC were found to have a higher incidence of pouchitis (58.5% vs 15.0%, P < 0.001) and CARP (24.5% vs 2.5%, P = 0.002) and a higher total peripouch fat area ( P = 0.030) and mesenteric peripouch fat area ( P = 0.022) at Level‐3. Univariate and multivariate analyses showed that diagnosis (UC vs FAP) and peripouch fat areas at Level‐3 and Level‐5 were independent risk factors for CARP. With propensity score matching, 38 pairs of patients with UC and FAP were matched successfully. After matching, patients with UC were found to have higher total peripouch fat area and higher mesenteric peripouch fat area at Level‐3, and a higher incidence of pouchitis (57.9% vs 13.2%, P < 0.001) and CARP (23.7% vs 2.6%, P = 0.007). Conclusion: Our study demonstrates that patients with UC have more peripouch fat than those with FAP, which may explain the difference in the frequency of pouchitis and CARP between these groups of patients.